Frozen in time : an epic story of survival, and a modern quest for lost heroes of World War II - Zuckoff, Mitchell. (Harper, 2013)
In Nov. 1942 a U.S. cargo plane crashed into the Greenland ice cap, the B-17 sent on the search-and-rescue mission got caught in a storm and also crashed, miraculously all nine men aboard survived. A second rescue operation was launched, but the plane, the Grumman Duck, flew into a storm and vanished. The survivors of the B-17 spent 148 days fighting to stay alive while waiting for rescue by famed explorer Bernt Balchen. Then in 2012 the U.S. Coast Guard and North South Polar mount an expedition to solve the mystery of the vanished plane and recover the remains of the lost plane's crew.